2006
DOI: 10.1177/0022022106286925
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Discrimination, Social Support Networks, and Psychological Well-being Among Three Immigrant Groups

Abstract: The authors addressed the specific role of and contradictory results previously obtained regarding ethnic versus host support networks in influencing directly and/or buffering the impact of perceived discrimination on the well-being of immigrants. A nationwide adult probability sample ( N= 2,360) included Finnish repatriates and Russian and Estonian immigrants in Finland from Russia, Estonia, and other countries of the former Soviet Union. Perceived discrimination had a significant impact on psychological well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
220
3
19

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 281 publications
(254 citation statements)
references
References 43 publications
(50 reference statements)
12
220
3
19
Order By: Relevance
“…To include adoptees of Russian origin is reasonable because they form the largest ethnic group among international adoptees in Finland. When it comes to discrimination, several studies in Finland have shown that attitudes toward immigrants from Russia are seen to be negative and racist (e.g., Jasinskaja-Lahti et al, 2006;Puuronen, 2011).…”
Section: Racial/ethnic Discrimination and Psychological Well-beingmentioning
confidence: 99%
“…To include adoptees of Russian origin is reasonable because they form the largest ethnic group among international adoptees in Finland. When it comes to discrimination, several studies in Finland have shown that attitudes toward immigrants from Russia are seen to be negative and racist (e.g., Jasinskaja-Lahti et al, 2006;Puuronen, 2011).…”
Section: Racial/ethnic Discrimination and Psychological Well-beingmentioning
confidence: 99%
“…As a result, the deleterious effects of perceived discrimination may to some extent be buffered through identification with minority groups (see Schmitt & Branscombe, 2002). Furthermore, extensive social support increases migrant well-being and adjustment (Davis, Morris, & Kraus, 1998;Safdar, Struthers, & van Oudenhoven, 2009), in particular social networks which include members of the receiving society (Jasinskaja-Lahti, Liebkind, Jaakkola, & Reuter, 2006). Also, illustrating the importance of transnational social spaces as determinants of successful adaptation, ethnic networks abroad have been shown to increase migrant well-being (Jasinskaja-Lahti et al,…”
Section: Acculturation and Adaptation Of Migrantsmentioning
confidence: 99%
“…For low status migrants this process may lead to "downward assimilation" whereby young migrants join the most disadvantaged minorities at the bottom of society (Portes & Rumbaut, 2006), an outcome squarely at odds with early assimilationist views of upward mobility and integration in mainstream society. Migrants in low social positions have also been shown to experience greater acculturative stress and to be prone to unsuccessful adjustment (Jasinskaja et al, 2006;Polek, van Oudenhoven, & Ten Berge, 2008).…”
Section: )mentioning
confidence: 99%
“…It can have an impact on the cultural identity of immigrant youths, and their sense of belonging to or exclusion from the majority society (Phinney and Devich-Navarro 1997;Phinney et al 2001Phinney et al , 2006Jasinskaja-Lahti et al 2006). …”
Section: Everyday Encountersmentioning
confidence: 99%